1980
DOI: 10.1111/j.1471-4159.1980.tb06263.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Sialyltransferase Activity in the Synaptosomal Membranes Prepared from Calf Brain Cortex

Abstract: The possible occurrence of sialyltransferase activity in the plasma membranes surrounding nerve endings (synaptosomal membranes) was studied, using calf brain cortex. The synaptosomal membranes were prepared by an improved procedure which provided: (a) a „nerve ending fraction” consisting of at least 85% well‐preserved nerve endings and containing only small quantities of membranes of intracellular origin; (b) a „synaptosomal membrane fraction” carrying high amounts of authentic plasma membrane markers (Na+‐K+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…However, other studies have claimed to detect certain glycosylation activities on the plasma membrane. Preti et al (51) have characterized a plasma membrane-anchored sialyltransferase that adds sialic acid to lactosylceramide and GM1 to make GM3 and GD1a. Sialidases have also been detected on the cell surface that remove sialic acids from gangliosides (11,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have claimed to detect certain glycosylation activities on the plasma membrane. Preti et al (51) have characterized a plasma membrane-anchored sialyltransferase that adds sialic acid to lactosylceramide and GM1 to make GM3 and GD1a. Sialidases have also been detected on the cell surface that remove sialic acids from gangliosides (11,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of ganglioside sialylation was previously reported in synaptosomal membrane from calf and rat brains and during the development of neuronal cell cultures (47)(48)(49). However, there was concern that cross-contamination of biochemically isolated membrane fractions may have occurred, and progress in this research area is still limited.…”
Section: Galnac-t But Not Gal-t2 Is Also Expressed At the Cell Surfacmentioning
confidence: 99%
“…Some information is also available about the in situ sialylation of gangliosides at the cell surface. The original report on the existence of a synaptosomal membrane sialyltransferase in calf brain (Preti et al. 1980) has been confirmed by metabolic studies in chicken embryos (Matsui et al.…”
Section: Local Plasma Membrane Events and Their Role In The Modulatiomentioning
confidence: 84%
“…About glycosphingolipids, long time ago it has been shown that synaptosomal membranes, a subset of neuronal membranes highly enriched in gangliosides, carry both a sialidase (Schengrund and Rosenberg 1970; Tettamanti et al. 1972, 1973, 1975), and a sialyltransferase (Preti et al. 1980) activity.…”
Section: Local Plasma Membrane Events and Their Role In The Modulatiomentioning
confidence: 99%